Nitrogen-Centered Radicals in Visible-Light-Promoted Reactions - Boselli, Monica F.; Medici, Fabrizio; Franco, Francesca (SynOpen, 2024)
Nitrogen-centered radicals (NCRs) have been known in the literature since the beginning of the 1900s, but only with the spread of photoredox catalysis, and in particular visible-light-mediated radical processes, has nitrogen-radical chemistry become more accessible via the in situ generation of such radicals under mild conditions. Historically, unlike their carbon counterparts, nitrogen radicals were not utilized widely in academia or industry due to a lack of efficient strategies for their production. Nowadays, NCRs are more established, and this graphical review highlights key publications from the literature, categorizing them by both the type of NCR and the type of reaction. Such nitrogen radicals can be divided into four different categories according to their electronic configuration, orbital structure and chemical behavior. Additionally, the reactivity of these radicals is mostly exploited via four main types of process: (i) intramolecular cyclization, (ii) intramolecular hydrogen atom abstraction, (iii) Norrish type I fragmentation, and (iv) intermolecular addition to π systems.
Keywords: nitrogen radicals; photoredox catalysis; visible-light-driven reactions; amidyl radicals; cyclizations; addition to π systems; hydrogen atom transfer